Development of life skill and professional practice (Vikas, 2014)
Life skills are essentially individual abilities that help in promoting mental well being and competence in people to deal with the various situations in life. this book presents various aspects of life skills including communication, self analysis, self development and study habits. These are crucial elements in determining one's personal and professional growth. Written in an interactive style this course book will help students inculcate the various life skill and enhance their acceptability and growth in this highly competitive world